Contact technique and concussions in the South African under-18 Coca-Cola Craven Week Rugby tournament - Hendricks, S.; O`connor, S.; Lambert, M.; Brown, J.; Burger, N.; Mc Fie, S.; Readhead, C.; Viljoen, W. (European Journal of Sport Science, 2015)
In rugby union, understanding the techniques and events leading to concussions is important because of the nature of the injury and the severity and potential long-term consequences, particularly in junior players. Proper contact technique is a prerequisite for successful participation in rugby and is a major factor associated with injury. However, the execution of proper contact technique and its relationship to injury has yet to be studied in matches. Therefore, the aim of this study was to compare contact techniques leading to concussion with a representative sample of similarly matched non-injury (NI) contact events. Injury surveillance was conducted at the 2011-2013 under-18 Craven Week Rugby tournaments. Video footage of 10 concussive events (5 tackle, 4 ruck and 1 aerial collision) and 83 NI events were identified (19 tackle, 61 ruck and 3 aerial collisions). Thereafter, each phase of play was analysed using standardised technical proficiency criteria. Overall score for ruck proficiency in concussive events was 5.67 (out of a total of 15) vs. 6.98 for NI events (n = 54) (effect size = 0.52, small). Overall average score for tackler proficiency was 7.25 (n = 4) and 6.67 (n = 15) for injury and NI tackles, respectively (out of 16) (effect size = 0.19, trivial). This is the first study to compare concussion injury contact technique to a player-matched sample of NI contact techniques. Certain individual technical criteria had an effect towards an NI outcome, and others had an effect towards a concussive event, highlighting that failure to execute certain techniques may substantially increase the opportunity for concussion.